Modeling the Key Factors Influencing the Collaboration in Fresh Produce Supply Chain - Fengzhao, Yin; Lo, May Chiun; Abang Azlan, Mohamad; Sin, Kit Yeng (Transnational Press London, 2024)
This study aims to elucidate the key factors driving collaboration within the fresh produce supply chain (FPSC) by conducting a comprehensive literature analysis and examining the interrelationships of these factors to pinpoint the most influential ones. Employing Interpretive Structural Modeling (ISM) alongside the Matrice d'Impacts Croisés Multiplication Appliquée à un Classement (MICMAC) method, and complemented by content analysis for factor identification, this research identifies a collaboration culture as the paramount factor influencing collaborative behaviors in FPSCs. The study's scope is confined to internal factors, omitting external influences like government policies, logistics infrastructure, and financial support. The insights gleaned are intended to guide managers and policymakers towards enhanced understanding and strategic decision making that foster collaboration in FPSCs, thus contributing to the achievement of sustainable development goals within this sector.